Molecular sexing from stools in spectacled bear (Tremarctos ornatus) - Caselli S., Caselli S. (2016)
The spectacled bear (Tremarctos ornatus) is a vulnerable species because of hunting and destruction of its environment. Also, it is difficult to monitor in the wild hampering the management and research efforts and therefore, the use of non-invasive samples such as faeces becomes a useful tool. The aim of this study was to develop a technique for sexing by the Polymerase Chain Reaction (PCR) using DNA extracted from exfoliated colon cells present in faecal samples. Seventeen samples (from 10 females and 7 males) were collected from bears of known sex reared in captivity in four institutions in Lima Peru. DNA extraction was done by using a specific kit for faecal samples. The concentration of extracted DNA varied between 20 to 30 ng. Using PCR, two gene sequences were evaluated: amelogenin with primers SE47-SE48 and sex-determining region in the Y chromosome (SRY) with primers SRYB5-SRYB3. Sex determination by the amelogenin gene was achieved in all bears (100%), whereas failed in all samples when using the SRY gene primers. It is concluded that there is 100% match with the amelogenin gene between the known and detected sex using the PCR of DNA extracted from faeces.